Financial Feasibility Evaluation of Jadu't Coffee as A Small and Medium Enterprise Business Model for Coffee Beverages - Sean Suleman; Ellan Jaya Adi Putra; Elisa Wowiling; Ryan Dharmawan; Budi Setiawan (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2025)
Purpose: This study aims to analyze the financial feasibility of Jadu't Coffee by transforming qualitative data from the owner, such as initial capital, purchasing patterns, and sales estimates, into financial calculations that include initial investment, COGS, cash flow, BEP, PP, ROI, ARR, NPV, IRR, and PI. Method: This study uses a descriptive qualitative approach through interviews, observations, and operational and financial analysis to transform the narrative data of business owners into measurable financial components. Result: The results of the study show that Jadu't Coffee is feasible based on financial indicators, with efficient initial investment, low COGS, positive cash flow, realistic BEP, and NPV, IRR, and PI values that meet investment feasibility criteria. These findings not only provide a basis for decision-making for business owners, but also have practical implications in the form of increased financial literacy, business planning skills, and greater access to financing. More broadly, this mentoring model can be replicated in MSME capacity building programs in Indonesia. Contribution: This study shows that MSME narrative data can be processed into measurable financial feasibility analyses as a basis for business decision-making. In addition to improving the financial literacy and planning of owners, this study also offers an applicable and replicable mentoring model for strengthening and sustaining MSMEs in Indonesia.